Morphological descriptions of laboratory reared larvae and post-larvae of the Australian shovel-nosed lobster Thenus australiensis Burton & Davie, 2007 (Decapoda, Scyllaridae) - Wakabayashi, K.; Phillips, Bruce (2016)
Complete larval development from newly hatched larvae up to the juvenile stage was successfully achieved in the Australian shovel-nosed lobster Thenus australiensis under laboratory conditions. The larvae of this species passed through four phyllosoma stages (each stage has a single instar), and developed into the first juvenile stage via a post-larval, nisto stage. The shortest and mean durations from hatching to metamorphosis at a water temperature of 25°C were 32 and 38 days, respectively. Morphologies of body and appendages for all four phyllosoma stages and the nisto stage were described. The phyllosomas were fed exclusively on the jellyfish Aurelia aurita throughout their culture. Our results indicate that jellyfish may be a viable diet for T. australiensis phyllosoma's in culture and may therefore be useful for commercial-scale lobster production.